Diagramación de los procesos de la bodega para la elaboración de un software de gestión, en la empresa Electconstru S.A. - Ruiz Salvatierra, Angel Omar (2019)
As a solution to the problem of inefficiency that ELECTCONSTRU S.A. has in its warehouse, this research raised the objective of "Diagram the processes of the warehouse for the development of a Management Software". An observation guide and an interview with the General Manager were used, applying a qualitative method, to know the main requirements; In addition, a questionnaire was applied to quantitatively determine the desirable aspects of the software, according to staff preferences. It was concluded with the elaboration of a design of the required management software, adjusted to the needs of ELECTCONSTRU SA, which gives importance to the “logistics chain” of all the elements involved in the provision of its services: users, suppliers, customers, Stock and inventory management